2022
DOI: 10.3389/fgene.2022.1032760
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of endogenous retroviral enhancers in mouse embryos derived from somatic cell nuclear transfer

Abstract: Endogenous retroviruses (ERVs) in the mammalian genome play diverse roles in embryonic development. These developmentally related ERVs are generally repressed in somatic cells and therefore are likely repressed in embryos derived from somatic cell nuclear transfer (SCNT). In this study, we sought to identify ERVs that are repressed in SCNT-derived morulae, which might cause previously unexplained embryonic deaths shortly after implantation. Our transcriptome analysis revealed that, amongst ERV families, ERVK w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Therefore, through reanalyzing the recently published transcriptome datasets of IVF embryos and SCNT embryos generated by combined approaches ( Kdm4d injection and Xist KO donor) (Fig. 5g ) [ 42 ], we found that downregulated genes in the SCNT group were associated with the top catalogs of known imprinting regulation and negative regulation of Wnt signaling, indicating disorders of Wnt activity existing even in SCNT embryos treated with combined approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, through reanalyzing the recently published transcriptome datasets of IVF embryos and SCNT embryos generated by combined approaches ( Kdm4d injection and Xist KO donor) (Fig. 5g ) [ 42 ], we found that downregulated genes in the SCNT group were associated with the top catalogs of known imprinting regulation and negative regulation of Wnt signaling, indicating disorders of Wnt activity existing even in SCNT embryos treated with combined approaches.…”
Section: Resultsmentioning
confidence: 99%